1996
DOI: 10.1002/(sici)1097-0142(19960601)77:11<2240::aid-cncr9>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

An aggressive therapeutic approach to carcinoma of the body and tail of the pancreas

Abstract: BACKGROUND Prognosis of patients with adenocarcinoma of the pancreatic body and tail is extremely poor. Anatomically, this part of the pancreas is thin, and cancerous invasion to the retropancreatic structures occurs easily. The majority of patients have residual tumor in the retroperitoneal tissues after conventional distal pancreatectomy. METHODS Between 1962 and 1979, 10 patients with carcinoma of the pancreatic body underwent simple distal pancreatectomy. Between 1980 and 1990, 22 patients including 7 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 8 publications
5
44
1
Order By: Relevance
“…Based on the high rate of recurrence, surgery alone seems to be inadequate for the treatment of patients with pancreatic cancer. Indeed, new clinical approaches such as, for example adjuvant chemotherapy plus radiation therapy (chemoradiation) after surgery or before surgery have been attempted and only a little improvement was observed in the survival rates of patients with pancreatic cancer, but the prognosis has remained worse than other cancers, such as breast cancer, colon cancer and gastric cancer (Ozaki et al, 1996;Schnall et al, 1996;Kamthan et al, 1997). In addition, most patients with pancreatic cancers are already unresectable when they are initially diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the high rate of recurrence, surgery alone seems to be inadequate for the treatment of patients with pancreatic cancer. Indeed, new clinical approaches such as, for example adjuvant chemotherapy plus radiation therapy (chemoradiation) after surgery or before surgery have been attempted and only a little improvement was observed in the survival rates of patients with pancreatic cancer, but the prognosis has remained worse than other cancers, such as breast cancer, colon cancer and gastric cancer (Ozaki et al, 1996;Schnall et al, 1996;Kamthan et al, 1997). In addition, most patients with pancreatic cancers are already unresectable when they are initially diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term results of radical distal pancreatectomy with en bloc resection of the celiac artery, with 1-and 2-year survival rates of 51% and 14% and the median survival of 12.2 months are not satisfactory, although they are significantly better than those of palliative surgery and are similar to reported survival in less advanced tumors [1][2][3][4]6,7,18]. The fact that the majority of treatment failures were due to hepatic metastases indicates a need for more effective adjuvant therapy against hepatic metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the rates of positive microscopic margins were 32 to 64% [4,5,7] and retroperitoneal recurrence accounted for 78 to 83% [6,18] of all recurrences, despite less advanced local disease. It has been suggested that this operation may help control local spread of advanced cancer of the body of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations